ضمانات رأس المال في استثمار أموال وقف النقود : دراسة فقهية - بن الزاوي، صهيب (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This thesis aims to investigate the issue of capital insurances in investing the endowment of cash funds (waqf al-Nuqud) in as much as it is believed to be, in general, one of the controversial issues in the contemporary Islamic finance institutions so as to conclude a legal provision on the issue, provided that it is based on licit evidence and in accordance with the objectives of Shari'ah. This study revolves around the investment of endowment of cash funds, and the means for protecting the capital generated from it. To this, the researcher has singled out a chapter on the legitimacy of endowment of cash funds. The second chapter focuses on disclosing the risks that may be caused by investing the endowment of cash funds, followed by a discussion of the views of the Muslim Jurists vis-à-vis the legal provisions of the means designed to protect the capital, with special reference to the reasons that made them differ in considering those means. The final chapter is meant to expose the most significant contemporary applications pertaining to the endowment of cash funds. The study adopted the inductive approach to track and collect statements made by scholars with regard to endowment of cash funds and to conclude from their views an endurable principle that can be applied in this study. The study also used the analytical and comparative approach to analyse the views of the Jurists and researchers on the subject at hand. In addition to an exhaustive study on juridical dimension of the subject, the study dealt with the objective dimension of it by making preference and choice of these views based upon the principles of shari'ah and that of endowment. This is followed by an investigation into the status quo of investing the endowment of cash funds today with reference to its different modes, including checks, shares and endowment funds. Hence, the study reached the following conclusions: that endowment of cash funds is allowed according the most authenticated statement by the Jurists; that the risks of investing endowed funds are so high that the characteristics of the Islamic system that allow them and the concept of endowment protection have become difficult to adapt. Moreover, the policy of insurances is meant for preserving and protecting propriety. Thus, this research looks into the means that can help achieve this goal by ensuring the ways of preservation in order to expel anything that can damage it. This policy calls for preservation for the interest of endowment. However, the adaptation of means and mechanisms, laid forth by the conventional investment system, or the imposition of new conditions has been a source of disagreement amongst the Jurists. These conditions aim at protecting the capital of the endowment and the propriety of the Ummah (Muslim community). The study also called for the implementation of this research in the endowment of cash funds in order to keep pace with economic developments. It prompted for developing means to protect the principles of endowment and the mechanisms of managing investment and endowment funds. In the end it called for reviving the tradition of endowment.